Pencegahan Serangan Kumbang Ambrosia Platypus Trepanatus (Chapman) Pada Balok Ramin (Gonystylus bancanus Kurz.) segar Dengan Lentrek 400 EC*) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
ABSTRACT Field experiment on prevention of fresh cut log ramin (Gonystylus bananas Kurz.) against ambrosia beetle Platypus trepanatus (Chapman) by spraying the log with Lentrek 400 EC termicide was conducted at Kenyala Camp, Kota Besi, PT. Inhutani III Sampit, Kalimantan Tengah, from November 1990 to January 1991. The objectives of the experiment were to investigate the efficacy and the protection period of Lentrek 400 EC termicide. There were total 22 treatments in this experiment. The treatments were five levels of Lentrek 400 EC concentrations in kerosene, two levels of Lentrek 400 EC concentrations in water, two levels of Cislin 2.5 EC concentrations in kerosene, kerosene and control, each of them with and without bark. Cislin, a commercial insecticide, was used as a comparison. Each treatment consists of one baiting log with three replication, and arranged in Radomized Block Design. Results showed that Lentrek 400 EC solution at 0.75 and 1.50% concentrations in kerosene were the same effective as Cislin 2.5 EC solution at 0.50 and 1.00% concentrations in kerosene to prevent fresh cut log ramin, with and without bark against ambrosia beetle P. trepanatus. Protection period ranged between 14 and 35 days.